АКСІОЛОГІЧНА КОМПЕТЕНТНІСТЬ МАЙБУТНЬОГО ВЧИТЕЛЯ ФІЗИЧНОГО ВИХОВАННЯ - Demincka, L (Continuing Professional Education: Theory and Practice, 2019)
The main purpose of the professional pedagogical preparation of future teachers of physical education consists in forming of readiness to professional activity on principles of axiology. This purpose can be realized upon the condition of formation of the future teachers’ of physical education axiological competence. Axiological competence is directed on the understanding and maintenance of health and personality of each student, as the highest value of pedagogical process.